(untitled) (Edad Media. Revista de Historia, 2018)
Fifteenth-century Castile, especially in the transition to Queen Isabella’s rule, is victim to a high-intensity violence caused by the nobility pursuing political objectives linked to their contradictory association to royal power and the royal domain. In this last case, the violence of the nobility is not just an expression of force but an instrument of legitimation for the same violence and its profits. Towns acted in a similar manner, manipulating the perception of that violence in order to blame the nobility. In addition, towns were able to enlist the cooperation of some noble lineages, who got involved in the active and public defense of urban interests in exchange for lucrative compensations. Given the nature of the towns and lordships involved, the Sierra of Castilla-La Mancha proves an ideal testing ground for this analytical model.